Soil chemical properties and maize yiel after application of organic and inorganic amendments to an acidic soil in southwestern Nigeria - Busari, M.A.=700 1 Salako, F.K.; Adetunji, M.T.
(En, Es)
Ilus., 33 ref.
Keywords: ENMIENDAS ORGANICAS; NUTRIENTES; HOJAS; ESTIERCOL; AVES; CAL; ABONOS NPK; MAIZ; PRODUCTIVIDAD; PROPIEDADES FISICO-QUIMICAS SUELO; TOXICIDAD; MANGANESO; NIGERIA; SPANISH JOURNAL OF AGRICULTURAL RESEARCH